2021
DOI: 10.1186/s13054-021-03521-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of cognitive impairment and brain insult after mechanical ventilation

Abstract: We conducted a systematic review following the PRISMA protocol primarily to identify publications that assessed any links between mechanical ventilation (MV) and either cognitive impairment or brain insult, independent of underlying medical conditions. Secondary objectives were to identify possible gaps in the literature that can be used to inform future studies and move toward a better understanding of this complex problem. The preclinical literature suggests that MV is associated with neuroinflammation, cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…3,5,6,8 Two recently published systematic reviews on MV associated with brain injury reported thirteen preclinical papers that describe hippocampal apoptosis and neuroinflammation as experimental findings linked to VABI. 9,10 In a porcine model, our group showed that even lung-protective MV settings were associated with brain injury after 50 hours of MV; 5 moreover, in the same study our group showed that serum concentrations of glial fibrillary acid protein (GFAP) and ubiquitin carboxy-terminal hydrolase L1 (UCHL1) were greater in the MV subjects than in the never-ventilated subjects, revealing an opportunity for the use of these markers for VABI. 5,6 It has been hypothesized that either an inflammatory or a neural pathway might lead to the development of VABI.…”
Section: Introduction: (416 Out Of 450 Words)mentioning
confidence: 75%
See 3 more Smart Citations
“…3,5,6,8 Two recently published systematic reviews on MV associated with brain injury reported thirteen preclinical papers that describe hippocampal apoptosis and neuroinflammation as experimental findings linked to VABI. 9,10 In a porcine model, our group showed that even lung-protective MV settings were associated with brain injury after 50 hours of MV; 5 moreover, in the same study our group showed that serum concentrations of glial fibrillary acid protein (GFAP) and ubiquitin carboxy-terminal hydrolase L1 (UCHL1) were greater in the MV subjects than in the never-ventilated subjects, revealing an opportunity for the use of these markers for VABI. 5,6 It has been hypothesized that either an inflammatory or a neural pathway might lead to the development of VABI.…”
Section: Introduction: (416 Out Of 450 Words)mentioning
confidence: 75%
“…Heart rate variability is a wellaccepted surrogate marker of the balance between vagal (parasympathetic) activity and sympathetic activity. 9 Root mean square of the standard deviation (RMSSD), a time-domain method of HRV analysis, was measured in our study (Figure 6). 9 All mechanically ventilated groups had two time periods analyzed during the 50 hours of the experiment, the first six hours after initiating the experiment (hours 0-6) and the last six hours before the end of the experiment (hours 44-50).…”
Section: Heart Rate Variability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Also, included studies did not report some important factors such as stroke risk factors that may have confounded the reported ABIs. A recent systematic review demonstrated that delirium and cognitive impairment were associated with mechanical ventilation, and therefore, it is possible that poor neurological outcome may be attributed to mechanical ventilation alone [ 69 ]. However, that study was not focused on subjects with ARDS and our study only included animals and patients with ARDS and provides a comprehensive review of ABI after ARDS.…”
Section: Discussionmentioning
confidence: 99%